DAMPAK ALOKASI DANA DESA BAGI PEMBANGUNAN DAERAH DAN KESEJAHTERAAN MASYARAKAT - Alfian Mujiwardhani; Heru Wibowo; Iman Tri Mulya (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2019)
This study aims to evaluate the impact of the Village Fund allocation on the improvement of regional development, which is measured by improvements in physical capital, human capital, economy, and community welfare (economic growth, poverty, and unemployment). The Difference in Difference (DID) method is applied to estimate the effects of village fund allocation by comparing the changes in outcome between the district that get village fund allocation (intervention group) and the cities that did not (control group). The results of the study show that the Village Fund has an impact on improving the achievement of outputs in infrastructure, education and health services, as well as improving economic performance, but has not been able to improve welfare indicators. The Village Fund is expected to be able to increase economic growth in the short term, but it has not yet affected poverty and unemployment.